World literature as discovery : expanding the world literary canon - Zhang, Longxi (Abingdon, Oxon ; New York : Routledge, 2024)
"The rise of world literature is the most noticeable phenomenon in literary studies in the twenty-first century. However, truly well-known and globally circulating works are all canonical works of European or Western literature, while non-European and even "minor" European literatures remain largely unknown beyond their culture of origin. World Literature as Discovery: Expanding the World Literary Canon argues that world literature for our time must go beyond Eurocentrism and expand the canon to include great works from non-European and "minor" European literatures. As much of the world's literature remains untranslated and unknown, the expansion will be an exciting process of discovery. By discussing fundamental questions around canon, circulation, aesthetic values, translation, cosmopolitanism and the literary universal, Zhang Longxi proposes a new and liberating concept of world literature that will shape world literature worthy of its name. This book speaks for a more inclusive idea of world literature, and shows students and scholars alike that all the literary traditions, particularly non-European traditions, will be able to make important contributions and expand the canon of world literature"--
Goethe and Weltliteratur -- The return to (world) literature -- Circulation and value judgment -- Canon and the classic -- World literature as discoveries -- Language, (un)translatability and world literature -- The challenge of writing a world literary history -- Literary universals -- The mirror of enigma and the mirror of magic -- Potion and poison : Chinese and Shakespearean dialectics -- Conclusion : world literature and cosmopolitanism.
Includes bibliographical references and index.
Keywords: Canon (Literature); Literature -- Philosophy